Characterizing epidemiological and genotypic features of Mycobacterium bovis infection in wild dogs (Lycaon pictus). Issue 6 (19th December 2020) - Meiring, Christina; Higgitt, Roxanne; Dippenaar, Anzaan; Roos, Eduard; Buss, Peter; Hewlett, Jennie; Cooper, Dave; Rogers, Peter; de Klerk‐Lorist, Lin‐Mari; van Schalkwyk, Louis; Hausler, Guy; van Helden, Paul; et al.
Abstract: Mycobacterium bovis (M. bovis) infects a wide range of wildlife species and has recently been discovered in the endangered African wild dog ( Lycaon pictus ). This study aimed to characterize the epidemiology of tuberculosis (TB) in wild dogs in endemic areas of South Africa. We describe 12 TB cases in wild dogs from Kruger National Park (KNP), Hluhluwe–iMfolozi Park (HiP) and a private facility in Hoedspruit from 2015 to 2017. Spoligotyping was used to identify the disease‐causing M. bovis strain in these cases, and whole‐genome sequencing was performed on 5 M . bovis isolates (KNP = 2 and HiP = 3) to investigate genomic diversity as well as the relationship to other isolates found in these geographical areas. Three distinct strain types were responsible for the M. bovis infections in this species. The SB0121 strain was observed in wild dogs from KNP, whereas SB0130 was responsible for infection in wild dogs from HiP. A novel strain, SB2681, was also identified in the HiP wild dogs. Whole‐genome sequence analysis suggests that different infection sources exist among these wild dogs and that inter‐species transmission most likely occurred between wildlife predators and prey located within shared geographical areas. This study highlights the importance of regular disease surveillance to identify and characterize potential threats for successful control of infection and protection of endangered species.